Formation, structure and properties of the starch-polyphenol inclusion complex: A review. (June 2021) - Deng, Nan; Deng, Zhong; Tang, Can; Liu, Chengmei; Luo, Shunjing; Chen, Tingting; Hu, Xiuting
Abstract: Background: Food is a complex system, which usually contains many different compounds. Thus, interaction between starch and other compounds is unavoidable and often significantly affects the properties of starch. Therefore, interaction between starch and other compounds has attracted considerable interest. Scope and approach: It is widely confirmed that starch can form the inclusion complex with a variety of small molecules, such as iodine, lipids, and aromatic compounds. Recently, it is found that starch and polyphenols can also form the inclusion complex. However, no related reviews are published. Thus, the formation, structure and properties of the starch-polyphenol inclusion complex are reviewed in this work. Specifically, this work describes the methods to prepare the inclusion complex, the techniques to identify the complex, protection of the complex on the polyphenol, digestibility and potential prebiotic activity of the complex. Key findings and conclusions: Formation of the starch-polyphenol inclusion complex can improve the stability and achieve slow release of the polyphenol, thus improving the bioavailability. Moreover, the starch-polyphenol inclusion complex is resistant to digestive enzymes. Thus, this complex is considered as the Type-5 resistant starch, which is similar to the starch-lipid complex. The resistance of the starch-polyphenol inclusion complex results from inhibition of polyphenols on digestive enzymes and the single helixes of starch formed in the complex. Thus, the starch-polyphenol complex may be more resistant than the starch-lipid complex. Moreover, this complex may have synergistic effects of polyphenols and traditional resistant starch without polyphenols in the prebiotic activity, which is a promising prebiotic ingredient. Highlights: Starch can form the inclusion or non-inclusion complex with polyphenols. Formation of the inclusion complex can improve the stability of the polyphenol. Formation of the starch-polyphenol complex can reduce digestibility of starch. The resistant inclusion complex is considered as Type-5 resistant starch. The starch-polyphenol inclusion complex may be a promising prebiotic.